Cytoplasmic ribonucleoprotein complexes, RNA helicases and coronavirus infection - Wang, Li; Guzmán, María; Sola, Isabel; Enjuanes, Luis; Zuñiga, Sonia (Frontiers in Virology, 2022)
RNA metabolism in the eukaryotic cell includes the formation of ribonucleoprotein complexes (RNPs) that, depending on their protein components, have a different function. Cytoplasmic RNPs, such as stress granules (SGs) or P-bodies (PBs) are quite relevant during infections modulating viral and cellular RNA expression and as key players in the host cell antiviral response. RNA helicases are abundant components of RNPs and could have a significant effect on viral infection. This review focuses in the role that RNPs and RNA helicases have during coronavirus (CoVs) infection. CoVs are emerging highly pathogenic viruses with a large single-stranded RNA genome. During CoV infection, a complex network of RNA-protein interactions in different RNP structures is established. In general, RNA helicases and RNPs have an antiviral function, but there is limited knowledge on whether the viral protein interactions with cell components are mediators of this antiviral effect or are part of the CoV antiviral counteraction mechanism. Additional data is needed to elucidate the role of these RNA-protein interactions during CoV infection and their potential contribution to viral replication or pathogenesis.